2011
DOI: 10.1073/pnas.1011915108
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic pollution of groundwater in Vietnam exacerbated by deep aquifer exploitation for more than a century

Abstract: Arsenic contamination of shallow groundwater is among the biggest health threats in the developing world. Targeting uncontaminated deep aquifers is a popular mitigation option although its long-term impact remains unknown. Here we present the alarming results of a large-scale groundwater survey covering the entire Red River Delta and a unique probability model based on three-dimensional Quaternary geology. Our unprecedented dataset reveals that ∼7 million delta inhabitants use groundwater contaminated with tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
182
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(186 citation statements)
references
References 39 publications
4
182
0
Order By: Relevance
“…As such, our understanding of the extent and mechanisms of deep arsenic contamination has remained incomplete. Evidence suggests that deep contamination in the Mekong Delta focus area is unlikely to have been caused by the only presently acknowledged mechanism: pumping-induced vertical migration of arsenic or dissolved organic carbon (DOC), which can trigger arsenic release, from the surface or shallow subsurface (6,7,(19)(20)(21). The number of wells above 10 μg/L in the deep zone is seven times greater than in the shallow zone.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As such, our understanding of the extent and mechanisms of deep arsenic contamination has remained incomplete. Evidence suggests that deep contamination in the Mekong Delta focus area is unlikely to have been caused by the only presently acknowledged mechanism: pumping-induced vertical migration of arsenic or dissolved organic carbon (DOC), which can trigger arsenic release, from the surface or shallow subsurface (6,7,(19)(20)(21). The number of wells above 10 μg/L in the deep zone is seven times greater than in the shallow zone.…”
Section: Resultsmentioning
confidence: 95%
“…"Dig deep to avoid arsenic" (3) has been touted as a safe answer to the provisioning of drinking water in Bangladesh, despite a lack of evidence that deep aquifers indeed remain uncontaminated under prescribed (4,5) or unregulated pumping. In fact, recent studies indicate that arsenic occurrence may be on the rise where deep aquifers are intensively pumped in parts of Bangladesh, West Bengal, India and the Red River Delta, in northern Vietnam (6)(7)(8). In some cases, isolated deep arsenic contamination may be caused by downward leakage through well bores.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the results of analyzed water samples exceeded the allowable level from 20 to 30 times higher. For example, in Phap Van groundwater wells, the ammonia level was 30 mg/L (see Dung, 2007;Winkel et al, 2011). A similar study conducted by Dan and Dzung (2002) also showed that the concentration of ammonia and oxidation are increasing with time and normally, concentrations in the upper aquifer is higher than in the lower aquifer in Hanoi area, indicating that pollutants migrate downward.…”
Section: Impacts Of Urbanization On Residential Water Demandmentioning
confidence: 72%
“…Logistic regression has been successfully used to assess the probability that As concentrations exceed a pre-defined threshold Twarakavi and Kaluarachchi, 2006;Winkel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%